Ovarian Surface Epithelium in Patients with Severe Ovarian Infertility: A Potential Source of Cells Expressing Markers of Pluripotent/Multipotent Stem Cells. (6th December 2011) - Virant-Klun, Irma; Skutella, Thomas; Stimpfel, Martin; Sinkovec, Jasna
Abstract : The aim of this study was to confirm the presence of stem cells in the ovarian surface epithelium of patients with premature ovarian failure and no mature follicles and oocytes. In these patients, small round cells of unknown origin expressing SOX-2 marker of pluripotency were observed among the epithelial cells just after the ovarian surface epithelium scraping. These cells were an integral part of the ovarian surface epithelium. When the scraped cells were cultured in a medium with added follicular fluid to provide some ovarian niche, primitive oocyte-like cells and typical round-shaped cell clusters positively stained on alkaline phosphatase, and markers of pluripotency, such as SOX-2 and SSEA-4, were developed. These markers were expressed early and also later in the culture. Single oocyte-like cells expressed genes OCT4A, SOX-2, NANOG, NANOS, STELLA, CD9, LIN28, KLF4, GDF3, and MYC, characteristic for pluripotent stem cells. The results of this study confirmed the presence of putative stem cells in the ovarian surface epithelium of these patients and provided some basis to create a stem cell line in the future.